Pendekatan Perenialisme dalam Pengembangan Kurikulum Pendidikan Agama Islam - Binti Astuti (Lembaga Sosial Rumah Indonesia, 2023)
The purpose of this research is to analyze the approach of perennialism in the development of the curriculum of Islamic religious education. The study uses library research, the object of the study using library data of books and journals as its source of data. The analysis of the study's data is descriptive. The perennial approach to the development of the curriculum of Islamic education consists of three main components: 1) strategic planning; 2) program planning; and 3) velivery plans. Of these three components, the perennial approach is an ideology that supports the evolution of academic curriculam.